1980
DOI: 10.1002/ardp.19803130806
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiinflammatory Activity of 3‐Substituted 4‐(4′‐Thiazolyl)‐Sydnones

Abstract: Sydnone derivatives with various substituents at C-4 of the phenyl ring and at C-2 of the thiazolyl ring were synthesised and tested for antiinflammatory activity. Five compounds have shown promising results. Synthese und entziindungshemmende Wirkung 3-subslituierter 4-(4'-Thiazolyl)-SydnoneSydnonderivate mit verschiedenen Substituenten in 4-Position des Phenyl-und 2-Position des Thiazolylringes wurden synthetisiert und auf entziindungshemmende Wirkung getestet. Fiinf der untersuchten Verbindungen zeigen vielv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It was found that 3-substituted-4-(thiazol-4-yl) sydnone had a weak to moderate activity [51]. On the other hand, the presence of 5-arylpyrazole at C4 of the sydnone ring resulted in a favourable antiinflammatory activity as an anti-arthritis, anti-edema, and analgesic with less ulcerogenic side effects.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…It was found that 3-substituted-4-(thiazol-4-yl) sydnone had a weak to moderate activity [51]. On the other hand, the presence of 5-arylpyrazole at C4 of the sydnone ring resulted in a favourable antiinflammatory activity as an anti-arthritis, anti-edema, and analgesic with less ulcerogenic side effects.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…For example, muscarinic agonists, histamine H3 antagonists, antitumoral, anti-inflammatory, and antimycobacterium tuberculosis agents containing a 1,2,4-oxadiazole ring are among them. [7][8][9][10][11][12] On the other hand, triazole rings have also attracted remarkable attention due to their biological activities such as antifungal, anti-convulsant agents and especially popular in designing anticancer agents. [13][14][15][16][17] 1,3-Dipolar cycloaddition route is a valuable process to assemble molecules having fragments in biologically active agents of five-membered nitrogen heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Various pharmacologically active heterocycles such as thiazoles [5], imidathiazoles [6], pyrazoles [7,8], 8-hydroxy quinolines, coumarins [9,10], benzimidazoles [11], triazinoindoles [12], indazoles, and other such rings have been incorporated at the position 4 of the 3-arylsydnones. Very few heterocycles on the 3-phenyl ring of 3-phenylsydnone have been reported so far [13] despite the fact that many of these compounds have exhibited considerable analgesic, anti-inflammatory, and antimicrobial properties in preliminary screening.…”
Section: Introductionmentioning
confidence: 99%